Perilaku Pencegahan Malaria di Kecamatan Rindi - Landi, Melkisedek; Radandima, Ester (JURNAL KESEHATAN PRIMER, 2021)
Background: Malaria endemic areas are generally remote villages with poor environmental conditions and low levels of prevention behavior. Objectives: The aim of the research is to determine individual, behavioral and environmental characteristics of malaria in Rindi District, East Sumba Regency. Methods: The research is descriptive correlational with a cross-sectional research design. With a sample of 56 people. Results: Age of Patients: <20 years 21 (31%), 21-30 years 11(16%), 31-40 years 16(29%), 40-60 years 11(16%) and >60 years 5 (7%). Occupation: Farmer 56(82%), Unemployed 9(13%), Entrepreneur 3(2%), Civil Servant 1(1%). Malaria cases based on examination results: Falciparum 48(71%), Vivax 6(12%) and Mix 12(17%). Preventive Behavior: Poor 1(1%), Fair 57(84%), Good 10(15%) with the highest preventive behavior being using mosquito nets (3.1). Environment: Poor 38(56%), Fair 25 (37%), Good 5(7%), with 100% bushes, 27(40%) near swamp 59 (87%) no wires for ventilation, low light 56( 82%), walls are not tight 50 (74%). The Spearman Test result is 0.942, meaning there is no relationship between environment and behavior.